METAPHOR IN PROVERB EXPRESSED IN ORAHUA OF WEDDING - Lies Dian M. Ndraha (Institut Pendidikan Tapanuli Selatan, 2021)
Metaphor is one of the figurative languages that takes two different things by identifying one with another. One of the oral literatures that makes the listener or reader interested to hear is orahua. Because speaker uses metaphor in proverbs in order to express certain intention, advices or message which is sometimes makes the listener get misunderstanding. This study attempts to find out the types of metaphor in proverb and the meaning of metaphor in proverb. This research design descriptive qualitative. The source of the data in this study is the proverb used by si’ulu and si’ilain orahua of wedding ceremony at Botohili Silambo village. The data were collected by using recording and interview. In the recording, the researcher only just takes the proverbs as the primary data. While in interview the researcher interviewed the speakers to get and clarify the meaning of the proverb. In analyzing the data, the researcher used metaphor theory that was introduced by Lakkof and Johnson (2003). Based on the research finding, the metaphor that used in orahua of wedding ceremony of was divided into 3 types, structural metaphor, orientational metaphor, and ontological metaphor. The researcher suggests to the reader to use the result of this research as reference to enrich their knowledge especially the proverbs, and take the advantages from this research.